Exploring of Nurses’ Needs of New Design Intravenous System Device to Support Nursing Care Effectively - Yesiana Dwi Wahyu Werdani; Hartono Pranjoto; Lanny Agustine; Diana Lestariningsih (Faculty of Nursing Universitas Padjadjaran, 2020)
Fluid control is important to support the success of therapy in the hospital. The existing features of the device currently do not fully support to ease the work of nurses. It is necessary to explore deeply the nurse’s need for the features of a new device intravenous system. The purpose of this study was to explore the nurse’s need for new design intravenous system devices to support nursing care effectively This was a qualitative study with thematic analysis methods. The participants were 20 nurses in Gotong Royong Hospital Surabaya taken by purposive sampling method. Data were collected by an in-depth interview. The instrument consists of structured questions. The interviews were recorded by a digital recorder. Ethical requirements are completed before data collection. This study found 4 themes consist of the economical price, multi-automatically system, flexible design, and simplicity. The nurse’s needs for a new design intravenous system device was designed more economical than today’s sophisticated device, and have more complete of automatic system, flexible and easy to use. These features match the needs expected by nurses and further assist in carrying out the nursing care process effectively and efficiently.